CONCEPTUAL DESIGN OF CONTROL ROD DRIVE MOTOR TYPE MAGNETIC JACK FOR NUCLEAR POWER PLANT - Fahmi Alfa Muslimu (Jurnal Forum Nuklir, 2021)
The Control Rod Drive Motor (CRDM) controls the reactor power of a G.A Siwabessy and automatically shuts it down during an emergency using a three-phase motor that drives a ball-nut spindle attached to the magnetic SCRAM through the transmission gear. However, there are several weaknesses associated with this design, such as the inability of the ball nut to rotate when a disturbance occurs at the motor limit switch continuously. This causes the threads on the control rod shaft to wear out due to friction and release from the holder. Therefore, this research aims to develop a CRDM with a magnetic jack for a nuclear plant, which moves the extension shaft and the control rod components vertically and linearly. The control rod's motor must pull, insert, hold, or drop it from any point. This conceptual design is the first step in determining prototyping design criteria with a magnetic jack to understand the working mechanism. The control rod gripping motion simulation was also presented using ANSYS Rigid Dynamics to reduce the failure at the design phase before prototyping. The simulation results showed no collision on each component capable of affecting the overall system performance. Therefore, the control rod motor functions properly in carrying out the pulling and lowering movements on 19.1 mm infrequency.